2021
DOI: 10.1111/cbdd.13850
|View full text |Cite
|
Sign up to set email alerts
|

Design strategies, SAR, and mechanistic insight of Aurora kinase inhibitors in cancer

Abstract: Aurora kinases (AURKs) are serine/threonine protein kinases that play a critical role during cell proliferation. Three isoforms of AURKs reported in mammals include AURKA, AURKB, AURKC, and all share a similar C‐terminal catalytic domain with differences in their subcellular location, substrate specificity, and function. Recent research reports indicate an elevated expression of these kinases in several cancer types highlighting their role as oncogenes in tumorigenesis. Inhibition of AURKs is an attractive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…Aurora kinase B (AURKB) is present in the centromeres in Prophase and Metaphase and it is located in the central mitotic spindle, being crucial for the segregation of chromosomes and cytokinesis (Zeitlin, Shelby and Sullivan 2001). AURK A and B expressions and kinase activities are elevated in a variety of human cancers and associated with high levels of proliferation and poor prognosis (Sankhe, Prabhu and Khan 2021). AURKB was proposed as a prognosis marker for GBM from a study that showed an overexpression in 25 GBMs samples and a correlation of its expression levels with survival (Zeng et al 2007).…”
Section: )mentioning
confidence: 99%
“…Aurora kinase B (AURKB) is present in the centromeres in Prophase and Metaphase and it is located in the central mitotic spindle, being crucial for the segregation of chromosomes and cytokinesis (Zeitlin, Shelby and Sullivan 2001). AURK A and B expressions and kinase activities are elevated in a variety of human cancers and associated with high levels of proliferation and poor prognosis (Sankhe, Prabhu and Khan 2021). AURKB was proposed as a prognosis marker for GBM from a study that showed an overexpression in 25 GBMs samples and a correlation of its expression levels with survival (Zeng et al 2007).…”
Section: )mentioning
confidence: 99%
“…Over the past few decades, intensive research efforts have led to the discovery of chemically diverse categories of Aurora kinase inhibitors. Few of these have translated to clinical trials but their lower efficacy, severe side effects, and increased cytotoxicity in treated patients have limited their success in the clinic. , There is, however, a renewed interest in Aurora A specific inhibitors because of recent discoveries of its synthetic lethal interactions with various tumor suppressor genes . In this regard, we screened a small library of natural and pseudo (semisynthetic) quinones to identify Aurora-A-specific inhibitors using an Aurora A kinase assay based on the phosphorylation of Aurora-A-substrate TACC3.…”
Section: Resultsmentioning
confidence: 99%
“…Its fusion inhibition was confirmed morphologically in 293T-ACE2-TMPRSS2 cells at high cell density (Figure 8). MLN8237 is an Aurora serine/threonine kinase inhibitor (Sankhe et al, 2021). It significantly inhibited fusion under all conditions apart from 293T-ACE2 cell fusion at physiological pH (Figure 6, Supplementary Figure S12).…”
Section: Lopsided Kite-shaped Molecules Are Potent Fusion Inhibitorsmentioning
confidence: 97%